Knowledge and reported symptoms of selected sexually transmitted infections among female secondary school students in Oyo State, Nigeria (2004)
This study examined the knowledge and reported symptoms related to some selected sexually transmitted injection (STIs) among Female Secondary School Students in Oyo State, Nigeria The participants (N - 928) were chosen through purposive sampling technique and a self-developed (42-item) validated questionnaire with 0.86 reliability was used as research instrument. Data collected were analysed with descriptive statistics of frequencies and percentage. Results showed that the level of sexual activity among the participants was significantly high. They had significant knowledge of gonorrhea disease. Knowledge of syphilis and HIV/A1DS was however, not significant. A significant number of the participants had reported symptoms related to gonorrhea within the last six months to this study. This result emphasis the need for change in risky behaviours. School campaigns should stress the need for behavioural change. Youth-friendly services, low-cost diagnosis and treatment techniques should also be made available to students, as this would be helpful in reducing the incidence of STIs. Health education would go a long way in controlling the spread of STIs among female adolescents in Nigeria.